Glue-free preparation method of stiff filter material for filter cartridge

By using ES fibers or multiple fibers with different melting points, hydrospuncture reinforcement and heating hard forming methods, the problem of softness and easy deformation of the filter material in the traditional filter cartridge is solved, the stiffness and fracture strength of the filter material are improved, the dust removal rate is enhanced, the preparation process is simplified, and the environmental protection is improved.

CN119565269APending Publication Date: 2025-03-07NANJING JIHUA 3521 ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411990726.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional filter cartridge filters have problems such as softness and easy deformation, which affects the filtration performance and usage effect. The large amount of hardener used has environmental problems and difficulty in operation.

Method used

Use ES fibers or at least two fibers with different melting points to form a filter material layer by loosening, blending, carding, meshing and needle-punching, and hydrospinning reinforcement and heating hard pressing molding to form hard pressing filter material and avoid using hard pressing agent.

Benefits of technology

It improves the stiffness and fracture strength of the filter material, enhances the dust removal rate, simplifies the preparation process, improves environmental protection, and avoids the problem of uneven absorption of hardener.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223591740000101
    Figure BDA0005223591740000101
  • Figure BDA0005223591740000111
    Figure BDA0005223591740000111
Patent Text Reader

Abstract

The invention relates to the technical field of filter materials, and particularly discloses a glue-free preparation method of a stiff filter material for a filter cartridge. The preparation method comprises the following steps that fiber raw materials are subjected to opening, blending, carding, lapping and needling to form a filter material layer, and the fiber raw materials comprise ES fibers or at least two kinds of fibers with different melting points; performing spunlace reinforcement on the filter material layer to obtain a felt material; the felt material is heated, and when the fiber raw material comprises ES fibers, the felt material is heated to 130-150 DEG C; when the fiber raw material comprises at least two kinds of fibers with different melting points, heating the felt material to the temperature between the melting point temperatures of the two kinds of fibers with different melting points; and carrying out heat preservation and hot rolling for 30-60 seconds, and cooling to room temperature to obtain the stiff filter material for the filter cartridge. The preparation method provided by the invention avoids the problem of non-uniform absorption of the stiffening agent by the filter material possibly caused by the use of the stiffening agent, is helpful for keeping high stiffness and breaking strength of the filter material, and also improves the environmental protection property and simplicity of the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of filter materials, and in particular to a method for preparing a stiff filter material for a filter cartridge without using glue. Background Art

[0002] In the field of environmental protection and industrial filtration, filter cartridges are widely used in the filtration process of various gases as a highly efficient filtration device. The performance of filter cartridges depends largely on the properties of their filter media. Traditional filter media often have problems such as softness and easy deformation, which to a certain extent affects the filtration performance and use effect of the filter cartridges. Stiffening finishing is a means to enhance the rigidity and stability of filter media fibers, thereby improving the filtration effect and service life of the filter cartridges.

[0003] In the related art, a method for stiffening the filter material of a filter cartridge substrate is disclosed, wherein the high temperature refers to the use temperature of the filter material of the substrate being 130°C-280°C; the specific steps are: Step 1, methyl silicone resin, hydrogenated silicone oil emulsion, and water are mixed at a mass fraction of 10%-30%: 15%-45: 25%-75% and stirred evenly to form a high temperature resistant stiffening agent; Step 2, immersing the filter cartridge substrate filter material in the above-mentioned high temperature resistant stiffening agent and rolling it dry with a roller, controlling the rolling rate to be 110-130%; Step 3, placing the rolled filter cartridge substrate filter material in an oven at 210±2°C for 10-15 minutes for cross-linking and curing.

[0004] In the above-mentioned filter material stiffening finishing method, a stiffening agent made of chemical reagents such as methyl silicone resin and hydrogen silicone oil emulsion is used to enhance the stiffness of the filter material through the steps of impregnation, rolling drying, cross-linking and curing. This process not only increases the difficulty of operation, but also has the problem of not being green and environmentally friendly due to the large amount of stiffening agent used. During the process of impregnation and rolling drying of the stiffening agent, if the filter material absorbs the stiffening agent unevenly, the stiffness and breaking strength of the filter material may also deteriorate. Summary of the invention

[0005] In order to improve the stiffness and breaking strength of the filter material, improve the environmental friendliness of the preparation method, and reduce the operational difficulty of the preparation method, the present application provides a glue-free preparation method for a stiff filter material for a filter cartridge.

[0006] The present application provides a method for preparing a stiff filter material for a filter cartridge without glue, which adopts the following technical solution:

[0007] A method for preparing a stiff filter material without glue for a filter cartridge comprises the following steps:

[0008] Preparation of filter material layer: opening, blending, combing, laying and needle punching the fiber raw materials to form a filter material layer, wherein the fiber raw materials include ES fiber or at least two fibers with different melting points;

[0009] Reinforcement: The filter material layer is reinforced by hydroentanglement to obtain a felt material;

[0010] Stiffening molding: heating the felt material, when the fiber raw material includes ES fiber, heating the felt material to 130-150°C; when the fiber raw material includes at least two fibers with different melting points, heating the felt material to a temperature between the melting points of the two fibers with different melting points; hot rolling for 30-60s, cooling to room temperature, and obtaining a stiff filter material for the filter cartridge.

[0011] By adopting the above technical scheme, ES fiber or at least two fibers with different melting points are selected. ES fiber is a fiber composited by polypropylene and polyethylene. When ES fiber is heated, a part of the components can soften and melt, and when the two fibers with different melting points are heated to the temperature between their melting points, the fiber with low melting point will melt first, while the fiber with high melting point will remain in solid state. During the heating process, these partially melted components will form bonding points to bond the fibers in the filter material layer together. This bonding effect not only enhances the structural stability of the filter material, but also makes the filter material show stiff characteristics in the macroscopic view. At the same time, through the step of heat preservation hot rolling, the bonding and fusion between the fibers can be further promoted, making the filter material more stiff. During the hot rolling process, the partially melted components will flow and fill the gaps between the fibers to form a more compact structure. After cooling to room temperature, the bonding points in the filter material will solidify, thereby forming a filter material with stiff characteristics. This structure not only improves the stiffness and breaking strength of the filter material, but also enhances its dust removal rate. Therefore, the preparation method of the present application avoids the problem of uneven absorption of the stiffening agent by the filter material that may be caused by the use of the stiffening agent, helps the filter material maintain a high stiffness and breaking strength, and also improves the environmental friendliness of the preparation method. The preparation process does not require steps such as impregnation, rolling drying, cross-linking and curing, and is more convenient.

[0012] In a specific embodiment, the fiber raw material includes A fiber and PP fiber, and the A fiber is any one of polyester fiber, PPS fiber, aramid fiber, and PI fiber; in the stiffening forming step, the felt material is heated to 90-110°C.

[0013] By adopting the above technical solutions, polyester fiber, PPS fiber, aramid fiber and PI fiber each have unique properties, such as strength, temperature resistance, chemical corrosion resistance, etc., which enables the filter material to be customized according to the needs of specific application scenarios. During the heating process at 85-110℃, the PP fiber can soften and melt to form stable bonding points, which can not only optimize the pore structure and distribution of the filter material, enhance the structural stability of the filter material, but also help maintain the stiffness and breaking strength of the filter material.

[0014] In a specific embodiment, the weight ratio of A fiber to PP fiber in the fiber raw material is 1:(0.4-0.8).

[0015] By adopting the above technical solution, the present application found that the dust removal rate of the filter material can be further improved by using the two fibers in the above ratio. This may be because the filter material structure formed in the above ratio has better dust removal performance.

[0016] In a specific embodiment, the PP fiber is prepared according to the following steps:

[0017] After cleaning and drying the PP masterbatch, mix it with glycidyl methacrylate and benzoyl peroxide, heat it to 150-180°C, melt blend it, and obtain a molten material;

[0018] The molten material is electrospun to obtain PP fibers.

[0019] By adopting the above technical solution, after the mixture of PP masterbatch, glycidyl methacrylate and benzoyl peroxide is melted, glycidyl methacrylate can be grafted onto the molecular chain of PP under the initiation of benzoyl peroxide, and polar groups are introduced into the molecular chain of PP to improve the adhesion between PP fiber and other fibers and enhance the strength of PP fiber. This helps PP fiber to form a more stable connection with other fibers after melting and solidification, further enhancing the stiffness and breaking strength of the filter material.

[0020] In a specific embodiment, the weight ratio of the PP masterbatch, glycidyl methacrylate and benzoyl peroxide is 100:(5-15):(0.1-0.25).

[0021] By adopting the above technical solution, the present application has found through experiments that the strength of the PP fibers prepared by the above raw material ratio is relatively high, and the filter material prepared by using such PP fibers has relatively high stiffness and breaking strength. This may be because, within the above ratio range, the melt blending process is more stable, reducing the problems of uneven viscosity and decreased thermal stability caused by improper component ratios, and the strength and adhesion of the PP fibers are relatively high.

[0022] In a specific embodiment, the PP masterbatch comprises the following raw materials in parts by weight: 80-100 parts of PP resin, 10-20 parts of ethoxylated alkylamine, 3-8 parts of plasticizer, and 2-5 parts of stabilizer.

[0023] By adopting the above technical solution, the ethoxylated alkylamine has good conductivity, which can enhance the antistatic performance of the PP masterbatch, thereby improving the antistatic performance of the filter material. The plasticizer can reduce the melting temperature of the PP masterbatch, improve its fluidity and processing performance, and make the melt blending process smoother. The stabilizer can improve the mechanical properties and processing performance of the PP masterbatch. Therefore, by using the PP masterbatch with the above raw material ratio, PP fibers with better antistatic performance and flexibility can be prepared, thereby further improving the breaking strength and safety of the filter material.

[0024] In a specific embodiment, the plasticizer is diisononyl phthalate.

[0025] By adopting the above technical solution, diisononyl phthalate can effectively reduce the glass transition temperature of PP resin, making it softer and easier to process. Moreover, diisononyl phthalate has good compatibility with PP resin and can be evenly dispersed in the resin.

[0026] In a specific embodiment, the stabilizer includes zinc stearate and hindered amine in a weight ratio of 1:(0.6-1.2).

[0027] By adopting the above technical solution, zinc stearate and hindered amine have good compatibility in PP resin and can form a uniform dispersion system. Zinc stearate can reduce the melt viscosity of PP resin, improve its fluidity, and make the melt blending process smoother. At the same time, hindered amine helps to reduce the thermal degradation of PP resin during processing. The present application has found through experiments that the PP fiber prepared by using PP resin with zinc stearate and hindered amine within the above weight ratio range can further improve the breaking strength of the filter material, which may be because the above raw material ratio can improve the flexibility of PP fiber.

[0028] In a specific embodiment, the PP masterbatch is prepared according to the following steps:

[0029] The PP resin, the ethoxylated alkylamine, the plasticizer and the stabilizer are uniformly mixed to obtain a mixture;

[0030] melt-blending the mixture to obtain a melt;

[0031] The melt is extruded and granulated to obtain PP masterbatch.

[0032] By adopting the above technical solution, the PP resin, the ethoxylated amine antistatic agent, the plasticizer and the stabilizer are firstly uniformly mixed, which helps various additives to be uniformly dispersed in the PP resin.

[0033] In summary, this application has the following beneficial effects:

[0034] 1. The preparation method of the present application avoids the problem of uneven absorption of the stiffening agent by the filter material that may be caused by the use of the stiffening agent, helps the filter material maintain a high stiffness and breaking strength, and also improves the environmental friendliness of the preparation method. The preparation process does not require steps such as impregnation, rolling drying, cross-linking and curing, and is more convenient.

[0035] 2. In the present application, it is preferred to use a combination of any one of polyester fiber, PPS fiber, aramid fiber, PI fiber and PP fiber as the fiber raw material, which helps to further improve the stiffness and breaking strength of the filter material.

[0036] 3. This application preferably uses PP masterbatch with a specific raw material ratio, which can further improve the breaking strength and safety of the filter material. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0038] Example

[0039] Example 1

[0040] This embodiment provides a method for preparing a stiff filter material for a filter cartridge without glue, comprising the following steps:

[0041] ES fiber (Jinyou, 2D*38mm) was opened, blended, carded, laid, and needled at a needle density of 80 needles / cm 2 , the needle puncture depth is 13mm, forming a filter material layer;

[0042] The filter material layer was hydroentangled with 5 hydroentanglement heads, the hydroentanglement pressure was 310 bar, and the vehicle speed was 5.5 m / min to obtain a felt material;

[0043] The felt material is heated to 140° C., then maintained at 140° C., hot-rolled for 45 seconds, and then naturally cooled to room temperature to obtain a stiff filter material for a filter cartridge.

[0044] Example 2

[0045] The only difference between this embodiment and embodiment 1 is that the felt material is heated to 130° C., then maintained at 130° C., hot-rolled for 60 seconds, and then naturally cooled to room temperature to obtain a stiff filter material for a filter cartridge.

[0046] Example 3

[0047] The only difference between this embodiment and embodiment 1 is that the felt material is heated to 150° C., then maintained at 130° C., hot-rolled for 30 seconds, and then naturally cooled to room temperature to obtain a stiff filter material for a filter cartridge.

[0048] Example 4

[0049] This embodiment provides a method for preparing a stiff filter material for a filter cartridge without glue, comprising the following steps:

[0050] The fiber raw materials are opened, blended, combed, laid and needled. The needle density is 80 needles / cm 2 The needle punching depth is 13mm to form a filter material layer. The fiber raw materials include polyester fiber (Longfeng Chemical Fiber, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) with a weight ratio of 10:6.

[0051] The filter material layer was hydroentangled with 5 hydroentanglement heads, the hydroentanglement pressure was 310 bar, and the vehicle speed was 5.5 m / min to obtain a felt material;

[0052] The felt material is heated to 100° C., then maintained at 100° C., hot-rolled for 45 seconds, and then naturally cooled to room temperature to obtain a stiff filter material for a filter cartridge.

[0053] Example 5

[0054] The only difference between this embodiment and Embodiment 4 is that the fiber raw material includes polyester fiber (Longfeng Chemical Fiber, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 10:2.

[0055] Example 6

[0056] The only difference between this embodiment and Embodiment 4 is that the fiber raw material includes polyester fiber (Longfeng Chemical Fiber, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 10:4.

[0057] Example 7

[0058] The only difference between this embodiment and Embodiment 4 is that the fiber raw material includes polyester fiber (Longfeng Chemical Fiber, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 10:8.

[0059] Example 8

[0060] The only difference between this embodiment and Embodiment 4 is that the fiber raw material includes polyester fiber (Longfeng Chemical Fiber, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 1:1.

[0061] Example 9

[0062] The only difference between this embodiment and embodiment 4 is that the fiber raw material includes PPS fiber (Huvis, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 10:6.

[0063] Example 10

[0064] The only difference between this embodiment and Embodiment 4 is that the fiber raw material includes aramid fiber (Putek, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 10:6.

[0065] Embodiment 11

[0066] The only difference between this embodiment and Embodiment 4 is that the fiber raw material includes PI fiber (Wenqi, 1.5D*32mm) and PP fiber (Tonghui, diameter 25um, length 15mm) in a weight ratio of 10:6.

[0067] Example 12

[0068] The only difference between this embodiment and embodiment 4 is that the felt material is heated to 90°C, then maintained at 90°C, hot-rolled for 60 seconds, and then naturally cooled to room temperature to obtain a stiff filter material for a filter cartridge.

[0069] Example 13

[0070] The only difference between this embodiment and embodiment 4 is that the felt material is heated to 110° C., then maintained at 110° C., hot-rolled for 30 seconds, and then naturally cooled to room temperature to obtain a stiff filter material for a filter cartridge.

[0071] Embodiment 14

[0072] The only difference between this embodiment and embodiment 4 is that the PP fiber of this embodiment is prepared according to the following steps:

[0073] First, PP masterbatch was prepared, which included the following raw materials: 90 kg PP resin, 15 kg ethoxylated alkylamine, 5 kg diisononyl phthalate, and 4 kg zinc stearate.

[0074] The PP resin, ethoxylated alkylamine, diisononyl phthalate and zinc stearate are uniformly mixed to obtain a mixture.

[0075] The mixture was heated to 175°C and melt-blended to obtain a melt.

[0076] The melt is extruded and granulated to obtain PP masterbatch.

[0077] Then, PP fiber was prepared. The PP masterbatch was washed with water, dried, mixed with PP masterbatch, glycidyl methacrylate and benzoyl peroxide in a weight ratio of 100:10:0.2, heated to 165° C., melt-blended, and obtained a molten material.

[0078] The molten material was electrospun to obtain PP fibers (25 μm in diameter and 15 mm in length).

[0079] Embodiment 15

[0080] The only difference between this embodiment and Embodiment 14 is that, during the preparation process of PP masterbatch, the PP masterbatch includes the following raw materials: 80 kg of PP resin, 20 kg of ethoxylated alkylamine, 8 kg of diisononyl phthalate, and 5 kg of zinc stearate.

[0081] Example 16

[0082] The only difference between this embodiment and Embodiment 14 is that, in the preparation process of PP masterbatch, the PP masterbatch includes the following raw materials: 100 kg of PP resin, 10 kg of ethoxylated alkylamine, 3 kg of diisononyl phthalate, and 2 kg of zinc stearate.

[0083] Embodiment 17

[0084] The only difference between this embodiment and embodiment 14 is that, in the process of preparing the PP masterbatch, zinc stearate is replaced by an equal amount of a mixture of zinc stearate and a hindered amine (BASF 944) in a weight ratio of 1:1.

[0085] Embodiment 18

[0086] The only difference between this embodiment and Embodiment 14 is that, in the process of preparing PP fiber, the PP masterbatch is washed with water, dried, mixed in a weight ratio of 100:5:0.25 among the PP masterbatch, glycidyl methacrylate and benzoyl peroxide, heated to 165° C., and melt-blended to obtain a molten material.

[0087] Embodiment 19

[0088] The only difference between this embodiment and Embodiment 14 is that, in the process of preparing PP fiber, the PP masterbatch is washed with water, dried, mixed in a weight ratio of 100:15:0.1 among the PP masterbatch, glycidyl methacrylate and benzoyl peroxide, heated to 165° C., and melt-blended to obtain a molten material.

[0089] Embodiment 20

[0090] The only difference between this embodiment and Embodiment 14 is that, in the process of preparing PP fiber, PP masterbatch, glycidyl methacrylate and benzoyl peroxide are mixed in a weight ratio of 100:10:0.2, heated to 150° C., and melt-blended to obtain a molten material.

[0091] Embodiment 21

[0092] The only difference between this embodiment and Embodiment 14 is that, in the process of preparing PP fiber, PP masterbatch, glycidyl methacrylate and benzoyl peroxide are mixed in a weight ratio of 100:10:0.2, heated to 180° C., and melt-blended to obtain a molten material.

[0093] Comparative Example

[0094] Comparative Example 1

[0095] The only difference between this comparative example and Example 1 is that the ES fiber (Jinyou, 2D*38mm) is replaced by an equal amount of polypropylene fiber (2D*38mm).

[0096] Comparative Example 2

[0097] The only difference between this comparative example and Example 1 is that the ES fiber (Jinyou, 2D*38mm) is replaced by an equal amount of polyethylene fiber (2D*38mm).

[0098] Comparative Example 3

[0099] The only difference between this comparative example and Example 4 is that the fiber raw material only includes polyester fiber (Longfeng chemical fiber, 1.5D*32mm).

[0100] Comparative Example 4

[0101] The only difference between this comparative example and Example 4 is that the fiber raw material only includes PP fibers (tonghui, diameter 25um, length 15mm).

[0102] Performance testing

[0103] The following performance tests were performed on the stiff filter materials for filter cartridges prepared in Examples 1-21 and Comparative Examples 1-4:

[0104] The 25°C stiffness (mN) of the stiff filter material used in the filter cartridge is tested using a stiffness tester.

[0105] According to GB / T12625-1990, the dust removal rate of the stiff filter media used in the filter cartridge is tested.

[0106] According to GBT3923.1-1997, test the breaking strength (N) of the composite filter material flame retardant filter cartridge.

[0107] The test results are shown in Table 1.

[0108] Table 1

[0109]

[0110]

[0111] Combining Examples 1-4 and Comparative Examples 1-4 and Table 1, it can be seen that compared with Examples 1-3, the stiffness, dust removal rate and breaking strength of Comparative Examples 1-2 are significantly reduced. Compared with Example 4, the stiffness, dust removal rate and breaking strength of Comparative Examples 3-4 are significantly reduced. This shows that the use of ES fiber or a fiber raw material made of a mixture of two fibers with different melting points and the preparation method of Example 1 or 4 can improve the stiffening effect, breaking strength and dust removal rate of the filter material.

[0112] Combining Examples 4-8 and Table 1, it can be seen that among Examples 4-8, the stiffness and breaking strength of Example 5 are the smallest, and the stiffness and breaking strength of Example 8 are both smaller than Example 7. This shows that within the weight ratio range of polyester fiber to PP fiber of 10:(4-8), the stiffness and breaking strength of the filter material can be further improved.

[0113] Combining Examples 4, 9-13 and Table 1, it can be seen that compared with Example 4, Examples 9-13 also have greater stiffness and breaking strength, and the dust removal rate is above 99.9%. This shows that using the fiber raw materials or process conditions of Examples 9-13, filter materials with good stiffness, breaking strength and dust removal rate can also be prepared.

[0114] Combining Examples 4, 14-21 and Table 1, it can be seen that compared with Example 4, the stiffness and breaking strength of Examples 14-21 are significantly increased, which shows that the PP fibers prepared using Examples 14-21 can help further improve the stiffness and breaking strength of the filter material.

[0115] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a stiff filter material for a filter cartridge without glue, characterized in that: The steps include: Preparation of filter material layer: opening, blending, combing, laying and needle punching the fiber raw materials to form a filter material layer, wherein the fiber raw materials include ES fibers or at least two fibers with different melting points; Reinforcement: The filter material layer is reinforced by hydroentanglement to obtain a felt material; Stiffening molding: heating the felt material, when the fiber raw material includes ES fiber, heating the felt material to 130-150°C; when the fiber raw material includes at least two fibers with different melting points, heating the felt material to a temperature between the melting points of the two fibers with different melting points; hot rolling for 30-60s, cooling to room temperature, and obtaining a stiff filter material for the filter cartridge.

2. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 1, characterized in that: The fiber raw materials include A fiber and PP fiber, and the A fiber is any one of polyester fiber, PPS fiber, aramid fiber and PI fiber. In the stiffening forming step, the felt material is heated to 90-110°C.

3. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 2, characterized in that: The weight ratio of A fiber to PP fiber in the fiber raw material is 1:(0.4-0.8).

4. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 2, characterized in that: The PP fiber is prepared according to the following steps: After cleaning and drying the PP masterbatch, mix it with glycidyl methacrylate and benzoyl peroxide, heat it to 150-180°C, melt blend it, and obtain a molten material; The molten material is electrospun to obtain PP fibers.

5. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 4, characterized in that: The weight ratio of the PP masterbatch, glycidyl methacrylate and benzoyl peroxide is 100:(5-15):(0.1-0.25).

6. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 4, characterized in that: The PP masterbatch comprises the following raw materials in parts by weight: 80-100 parts of PP resin, 10-20 parts of ethoxylated alkylamine, 3-8 parts of plasticizer, and 2-5 parts of stabilizer.

7. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 6, characterized in that: The plasticizer is diisononyl phthalate.

8. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 6, characterized in that: The stabilizer includes zinc stearate and hindered amine in a weight ratio of 1:(0.6-1.2).

9. The method for preparing a stiff filter material for a filter cartridge without glue according to claim 6, characterized in that: The PP masterbatch is prepared according to the following steps: The PP resin, the ethoxylated alkylamine, the plasticizer and the stabilizer are uniformly mixed to obtain a mixture; melt-blending the mixture to obtain a melt; The melt is extruded and granulated to obtain PP masterbatch.

Citation Information

Patent Citations

  • Compound filter membrane as well as processing device and method thereof

    CN104437108A

  • Novel filter material and preparation method thereof

    CN113846420A

  • Preparation method of polyester filter cartridge for flue gas defluorination and dust removal in electrolytic aluminum industry

    CN117225087A

  • Antibacterial PP synthetic cotton fiber filter material and application thereof

    CN117504440A

  • Air filter having electrostatically active nonwoven fabric inliners and their use

    US20030000389A1